Challenges of transhumanism in 21st century education: the soul of democracy on the ropes - Castillo , Paloma (Revista Complutense de Educación, 2023)
INTRODUCTION. Today’s fervent scientific and technological development needs to be governed by human values. Pedagogical and transhumanist discourses respond jointly to this purpose, in the face of a society that is in danger of both the abuse of progress and the renunciation of it. However, among the challenges of transhumanism are the possibilities of changing the most genuine condition of humanity. The deepest longings and the most important achievements require a controversial act of discernment present in every corner of current education. METHOD. A hermeneutic-reflexive methodology has been used to carry out an exploratory analysis of the main implications of transhumanism, as an intellectual and cultural movement, in 21st century education. RESULTS. In the light of what has been studied, three axes can be distinguished: time, capacity and freedom. We live under parameters of instantaneity, fluidity and accelerated performance, but we advocate slowness for human flourishing; we long for the consecration of intelligence, but we fear losing what makes us unique; we foresee the end of our limits, but we risk chaining our freedom. DISCUSSION. The resulting discussion revolves around the crisis of postmodernity and the deep scepticism that emerges about one of the ends of education: our own reason; the soul of democracy.